2005
DOI: 10.1111/j.1365-2958.2005.04663.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the one‐carbon metabolism regulon in Saccharomyces cerevisiae by Bas1p

Abstract: SummaryThe mechanisms mediating responses to glycine withdrawal in budding yeast were studied using a genome-wide profiling approach. A striking pattern of repressed expression of genes with an enrichment for those involved in one-carbon metabolism and AMP biosynthesis was revealed. Sequence analysis of the promoters for the most severely repressed genes identified a conserved sequence, TGACTC, a known binding site for the transcription factors Gcn4p and Bas1p. Loss of BAS1 abolished or significantly reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Full induction of RNR activity requires Dun1, and in a parallel pathway, Pop2 and Ccr4 (components of the Ccr4-Not complex) (Huang et al 1998;Zhao and Rothstein 2002;Mulder et al 2005;Woolstencroft et al 2006). In addition, there are several links between glycine metabolism and de novo purine biosynthesis (Subramanian et al 2005;Christensen and Mackenzie 2006). Consistent with this, gly1D mutants are HU sensitive and have reduced dNTP pools (Hartman 2007).…”
Section: Loh On Chromosome IIImentioning
confidence: 48%
“…Full induction of RNR activity requires Dun1, and in a parallel pathway, Pop2 and Ccr4 (components of the Ccr4-Not complex) (Huang et al 1998;Zhao and Rothstein 2002;Mulder et al 2005;Woolstencroft et al 2006). In addition, there are several links between glycine metabolism and de novo purine biosynthesis (Subramanian et al 2005;Christensen and Mackenzie 2006). Consistent with this, gly1D mutants are HU sensitive and have reduced dNTP pools (Hartman 2007).…”
Section: Loh On Chromosome IIImentioning
confidence: 48%
“…Under conditions of glycine induction Gelling et al (2004) noticed a similar pattern of C1 enzyme differential expression; however, Bas1 was not required for the observed effect in this case. In both of these studies the intact cytosolic serine hydroxymethyltransferase Shm2 (EC 2.1.2.1) was necessary for glycine-dependent changes in C1 enzyme expression (Gelling et al 2004;Subramanian et al 2005). Although contradicting evidence exists, results reported thus far demonstrate the dynamic control of C1 metabolism in eukaryotes.…”
mentioning
confidence: 68%
“…Two groups have independently shown that C1 enzymes are controlled dynamically by glycine at the transcriptional level. Upon glycine withdrawal many enzymes involved in C1 metabolism are strongly repressed, a regulatory event that requires the transcription factor Bas1 (Subramanian et al 2005). Under conditions of glycine induction Gelling et al (2004) noticed a similar pattern of C1 enzyme differential expression; however, Bas1 was not required for the observed effect in this case.…”
mentioning
confidence: 79%
“…The proteins that control phosphorylation of Pho2 under physiological conditions have not been identified, but it is known that the Cdc28 is able to phosphorylate Pho2 in vitro (Liu et al 2000). Note that the function of Pho2 is not restricted to phosphate signalling, as this cofactor is also involved in mating-type switching, through its interaction with Swi5 (Bhoite and Stillman 1998;Bhoite et al 2002), as well as in one-carbon metabolism and especially adenine synthesis, through interaction with Bas1 (Zhang et al 1997;Bhoite et al 2002;Subramanian et al 2005). The latter is of particular interest since it provides a link between phosphate signalling and adenylic nucleotide synthesis as will be discussed below.…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%